(untitled) (Modern Problems of Metallurgy, 2019)
The doping by isovalent impurities (first of all, germanium (Ge)) has been proposed for increasing of the silicon radiation resistance.The most convenient structure for experimental measurements of h21E degradation under irradiation is a test npn transistor IC with dielectric isolation, the radiation degradation of which completely determined by the properties of a uniformly doped n-type SiGe single crystal wafer.The purpose of this work was a comparative assessment of the h21E degradation of ICs test npn structures, fabricated on nSiGe with different Ge concentrations and base widths to the action of α-radiation to confirm the technological applicability of isovalently doped Ge silicon for the formation of device structures that work in the fields of ionizing radiation.The measurements were carried out on the CZ-Si, orientation <111> with ρ ≈ 0.2 Ω · cm, NOi ≈ 7 ∙ 1017 cm-3, NСi<5 ∙ 1016 cm-3, doped with germanium and the controls under identical conditions.The radiation sensitivity of npn structures fabricated on nSiGe was simulated using MathCAD technology. Using the experimental values of h21E before and after irradiation and using standard statistical methods, equations,describing the degradation of npn structures depending on the level of isovalent doping and the geometry of the vertical structure,were obtained. The dose dependence of h21E indicates a significant difference in the degradation rate of the amplifying properties of test transistor structures fabricated on silicon with different Ge contents.It was shown that the test planar transistor amplifying properties degradation rate depends nonlinearly on both the concentration of isovalent impurity and the dose of α-irradiation, and the nature of the dependence is determined by the width of the base of the device. The dependences confirm the possibility of nSiGe use for the manufacturing of discrete semiconductor devices resistant to ionizing radiation.